The Allelochemical MDCA Inhibits Lignification and Affects Auxin Homeostasis - Steenackers, Ward; Cesarino, Igor; Klíma, Petr; Quareshy, Mussa; Vanholme, Ruben; Corneillie, Sander; Kumpf, Robert Peter; Van de Wouwer, Dorien; Ljung, Karin; Goeminne, Geert; Novák, Ondřej; Zažímalová, Eva; et al. (Plant physiology, 2016)
The phenylpropanoid 3,4-(methylenedioxy)cinnamic acid (MDCA) is a plant-derived compound first extracted from roots of Asparagus officinalis and further characterized as an allelochemical. Later on, MDCA was identified as an efficient inhibitor of 4-COUMARATE-CoA LIGASE (4CL), a key enzyme of the general phenylpropanoid pathway. By blocking 4CL, MDCA affects the biosynthesis of many important metabolites, which might explain its phytotoxicity. To decipher the molecular basis of the allelochemical activity of MDCA, we evaluated the effect of this compound on Arabidopsis thaliana seedlings. Metabolic profiling revealed that MDCA is converted in planta into piperonylic acid (PA), an inhibitor of CINNAMATE-4-HYDROXYLASE (C4H), the enzyme directly upstream of 4CL. The inhibition of C4H was also reflected in the phenolic profile of MDCA-treated plants. Treatment of in vitro grown plants resulted in an inhibition of primary root growth and a proliferation of lateral and adventitious roots. These observed growth defects were not the consequence of lignin perturbation, but rather the result of disturbing auxin homeostasis. Based on DII-VENUS quantification and direct measurement of cellular auxin transport, we concluded that MDCA disturbs auxin gradients by interfering with auxin efflux. In addition, mass spectrometry was used to show that MDCA triggers auxin biosynthesis, conjugation, and catabolism. A similar shift in auxin homeostasis was found in the c4h mutant ref3-2, indicating that MDCA triggers a cross talk between the phenylpropanoid and auxin biosynthetic pathways independent from the observed auxin efflux inhibition. Altogether, our data provide, to our knowledge, a novel molecular explanation for the phytotoxic properties of MDCA.
Keywords: homeostáza; vztah mezi dávkou a účinkem léčiva; geneticky modifikované rostliny; Plants, Genetically Modified; Indoleacetic Acids; Homeostasis; Coenzyme A Ligases; cinnamáty; Cinnamates; biosyntetické dráhy; hmotnostní spektrometrie; Dose-Response Relationship, Drug; Plant Roots; benzoáty; fenylpropionáty; kyseliny indoloctové; Benzoates; Phenylpropionates; Mass Spectrometry; Biosynthetic Pathways; lignin; Arabidopsis; Trans-Cinnamate 4-Monooxygenase; Lignin; konfokální mikroskopie; semenáček; 4-monooxygenasa kyseliny skořicové; Microscopy, Confocal; kořeny rostlin; Seedlings; koenzym A-ligasy